Trust, Risk, and Race in American Medicine - Sullivan, Laura Specker (The Hastings Center report, 2020)
There is ample evidence that patient mistrust toward the American medical system is to some extent associated with communal and individual experiences of racism. For groups who have faced exploitation and discrimination at the hands of physicians, the medical profession, and medical institutions, trust is a tall order and, in many cases, would be naive. Nevertheless, trust is often regarded as a central feature of the physician-patient relationship. In this article, I draw on empirical research, ethical theory, and clinical cases to propose one way that providers might address and, ideally, resolve mistrust when it arises in an immediate case. I describe how medical mistrust has been characterized empirically within medical and bioethics scholarship, and I provide an overview of theories of trust, arguing that they may be unable to account for the risks that providers must take in seeking to establish trust within many American medical institutions. Common assumptions in medical and bioethical scholarship on trust notwithstanding, caring and competence are not always enough to establish a trusting relationship between physician and patient. I suggest that, in an atmosphere of mistrust, comprehension of the existence and source of suspicion is essential to effective signaling of trustworthiness.